Structural Model of Personality Traits and Illness Perception with Functional Disability in Functional Somatic Syndromes in Patients with Coronary Artery Disease Based on the Mediating Role of Self-Care Behavior - Razaghpour, Mehdi; Taghiloo, Sadegh; Sharifnia, Hamid; Seyrafi, Mohammad Reza (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: Heart diseases, including coronary artery disease, are among the three main causes of death alongside cancer and stroke in most countries. The current study aimed to predict functional disability in functional somatic syndromes in patients with coronary artery disease based on personality traits and illness perception, considering the mediating role of self-care behavior. Methods and Materials: This study, with applied objectives and a correlational research design, was conducted using the structural equation modeling approach. The statistical population included all patients with coronary artery disease in the city of Amol in the year 2022, from which 250 individuals were purposefully selected. Data collection tools included the World Health Organization Disability Assessment Schedule (2014), the McCrae and Costa Personality Traits Questionnaire (1985), the Illness Perception Questionnaire (2006), and the Self-Care Questionnaire (2003). The statistical technique used was structural equation modeling with full latent variables. SPSS version 26, AMOS version 24, and R version 4.2.0 software were used for statistical data analysis. Findings: The results showed that all five personality dimensions, illness perception, and self-care significantly explain the variance in functional disability (P<0.01). Additionally, the mediating role of self-care behavior was significant in the relationship between functional disability and four personality dimensions: extraversion, openness to experience, agreeableness, conscientiousness, and illness perception (P<0.01). Conclusion: It can be concluded that functional disability in functional somatic syndromes in patients with coronary artery disease can be predicted based on their personality traits and illness perception, taking into account the mediating role of self-care behavior.